OPTIMALISASI PERAN KOMUNITAS BELAJAR DALAM IMPLEMENTASI KURIKULUM MERDEKA - Supriyanti, Yeti; Atikah, Cucu (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2024)
The purpose of this study is to explore the more optimal role of the learning community in supporting the implementation of the Independent Curriculum.The research method uses a qualitative approach with a descriptive method. Data were collected in text form through in-depth interviews, participatory observation, and documentation. The data validation process was carried out through triangulation of sources and methods to ensure the reliability and validity of the information obtained. This research was conducted from August to October 2024 in Bojonegara District, Serang Regency. Data analysis techniques were carried out qualitatively through the steps of data reduction, data presentation, and drawing conclusions.The results of the analysis show that optimizing the role of the learning community not only improves the quality of learning but also forms a more inclusive and responsive educational environment to students' needs. Optimizing the role of the learning community has been proven to not only improve the quality of learning but also form a more inclusive and responsive educational environment to students' needs. As a result, an important element in the successful implementation of the Independent Curriculum is the role of the learning community, which produces a generation that is better prepared to face future challenges.